General Anesthesia During Neurodevelopment Reduces Autistic Behavior in Adult BTBR Mice, a Murine Model of Autism - Cui, Jianchen; Park, Jiho; Ju, Xianshu; Lee, Yulim; Hong, Boohwi; Ahn, Jeonghoon; Kim, Yoon Hee; Ko, Youngkwon; Yoon, Seok-Hwa; Lim, Chaeseong; Lee, Sun Yeul; Huh, Sung-Oh; et al. (Frontiers in Cellular Neuroscience, 2021)
Preclinical studies suggest that repeated exposure to anesthetics during a critical period of neurodevelopment induces long-term changes in synaptic transmission, plasticity, and behavior. Such changes are of great concern, as similar changes have also been identified in animal models of neurodevelopmental disorders (NDDs) such as autism. Because of overlapping synaptic changes, it is also possible that anesthetic exposures have a more significant effect in individuals diagnosed with NDDs. Thus, we evaluated the effects of early, multiple anesthetic exposures in BTBR mice, an inbred strain that displays autistic behavior. We discovered that three cycles of sevoflurane anesthesia (2.5%, 1 hour) with 2-hour intervals between each exposure in late postnatal BTBR mice did not aggravate, but instead improved pathophysiological mechanisms involved with autistic behavior. Sevoflurane exposures restored E/I balance (by increasing inhibitory synaptic transmission), and increased mitochondrial respiration and BDNF signaling in BTBR mice. Most importantly, such changes were associated with reduced autistic behavior in BTBR mice, as sociability was increased in the three-chamber test and repetitive behavior was reduced in the self-grooming test. Our results suggest that anesthetic exposures during neurodevelopment may affect individuals diagnosed with NDDs differently.